2014
DOI: 10.17265/2161-6264/2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Thermal Properties of Starches Isolated from White and Pigmented Sorghum Landraces Grown in Hyper Arid Regions

Abstract: Abstract:The starches were isolated by alkaline extraction from white and red sorghum, predominant cultivars in the Sahara of Algeria. Morphological, thermal properties and amylose content of isolated starches were examined. The starches of two sorghum landraces of white and pigmented kernels growing in hyper arid environmental conditions showed significant differences in granule size, amylose content and thermal behavior which ultimately affect the physicochemical and functional properties. When observed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Sorghum starch existed in plant tissues in the form of granules whose characteristics of size, shape and form were distinctive to each botanical specie starch heterogeneity could be caused by the difference in developing environment or in genetic characteristic. The floury endosperm has more rounded starch granules whereas in the horny endosperm the angular granules are the predominant Boudries et al (2014). Therefore our results assumed that the endosperm in the examined sorghum varieties could be with horny endosperm and with high content of amylose.…”
Section: Shape and Size Of Starch Granulesmentioning
confidence: 65%
See 1 more Smart Citation
“…Sorghum starch existed in plant tissues in the form of granules whose characteristics of size, shape and form were distinctive to each botanical specie starch heterogeneity could be caused by the difference in developing environment or in genetic characteristic. The floury endosperm has more rounded starch granules whereas in the horny endosperm the angular granules are the predominant Boudries et al (2014). Therefore our results assumed that the endosperm in the examined sorghum varieties could be with horny endosperm and with high content of amylose.…”
Section: Shape and Size Of Starch Granulesmentioning
confidence: 65%
“…Gaffa et al (2004) noticed that the higher amount of large molecules was shown from red sorghum comparing with the white sorghum starch. Boudries et al (2014) found that the starch granule size varied between 6.33 and 39.91µm for whit sorghum and varied from 7.10 to 44.78µm for pigmented sorghum, size was nearly similar to those of corn and cassava.…”
Section: Shape and Size Of Starch Granulesmentioning
confidence: 87%
“…It is clear that the initial saccharification rates of corn starch are twice as high as that of white sorghum starch. This is due to the difference of physiochemical and functional properties including amylose/amylopectin ratio 23/77 for white sorghum starch (Boudries et al., 2014) and 28/72 for corn starch (Jobling, 2004) and other thermal and rheological properties.…”
Section: Resultsmentioning
confidence: 99%
“…The feasibility of the glucose syrups production using starch isolated from white sorghum landrace was the main objective to substitute imported corn starch and syrups. White sorghum landrace is the most abundant and appreciable cultivars in these hyper‐arid regions and previous studies showed its potential interest in food conversions (Boudries et al., 2009, 2014). In addition, it stimulates local production to ensure the development of the Saharan regions.…”
Section: Introductionmentioning
confidence: 99%
“…[36] Crystallinity values were in the range of 23.5-39.0%, with no differences by sorghum color (data not shown). Conversely, Boudries et al [37] reported different values for white (22.7%) and red (28.9%) sorghum starches.…”
Section: Physicochemical Properties Of Isolated Starches From Differementioning
confidence: 96%